IgG4-related hypertrophic pachymeningitis presenting with marked dural thickening, widespread white matter changes, and rectus gyrus transdiaphragmatic herniation into the sella turcica: a case report - Ogawa, Takashi; Yamashiro, Kazuo; Tsutsumi, Satoshi; Takai, Isamu; Kiuchi, Reika; Hirata, Yuto; Nakamura, Ryota; Nakahara, Toshiki; Watanabe, Masao; Hattori, Nobutaka; Hatano, Taku; Urabe, Takao (Frontiers in Immunology, 2026)
IntroductionIgG4-related disease is a clinically significant immune-mediated condition that can involve multiple organs. In the central nervous system, IgG4-related hypertrophic pachymeningitis is characterized by dural thickening, and the resulting mass effect may lead to various neurological deficits and characteristic imaging findings.Case descriptionA 54-year-old Japanese man presented with a 6-month history of slowly progressive right-sided visual impairment and visual field loss. Neurological examination revealed no abnormalities other than reduced visual acuity and visual field defects. Cranial magnetic resonance imaging revealed marked dural thickening extensively involving the bilateral frontotemporal regions, widespread frontal white matter lesions, and transdiaphragmatic herniation of the rectus gyrus into the sella turcica. The serum IgG4 level was elevated (429 mg/dL), and a dural biopsy revealed inflammatory cell infiltration with IgG4-positive plasma cells, leading to a diagnosis of IgG4-related hypertrophic pachymeningitis. Systemic evaluation, including laboratory screening and trunk computed tomography, revealed no other organ involvement apart from cervical and hilar lymphadenopathy. The patient responded well to steroid treatment (intravenous methylprednisolone followed by tapered oral prednisolone), with gradual improvement of the dural thickening, white matter lesions, rectus gyrus herniation, and visual field defects over 3 months. The serum IgG4 level decreased to 70.3 mg/dL.DiscussionThis case was characterized by pronounced dural thickening, widespread white matter lesions, and unprecedented rectus gyrus herniation into the sella turcica, a combination of features not previously reported. Neurologists should consider IgG4-related disease in the differential diagnosis of hypertrophic pachymeningitis accompanied by white matter lesions because early recognition and treatment may prevent irreversible neurological damage.